2009
DOI: 10.1080/13880200802578983
|View full text |Cite
|
Sign up to set email alerts
|

Variation of total hypericin, phenolic and flavonoid compounds inHypericum triquetrifoliumduring its phenological cycle

Abstract: The genus Hypericum (Hypericaceae) contains a variety of structurally diverse natural products which possess a wide array of biological properties. The present study examined quantitative variations in total hypericin, phenols, and flavonoids in Hypericum triquetrifolium Turra. in relation to phenological development. Plant material was harvested at different phenological stages (vegetative, full flowering, and mature fruiting stages). The amounts of bioactive compounds in whole shoots were assayed. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
2
15
0
1
Order By: Relevance
“…() with an enhanced of polyphenols content in the older sprouts. The difference in the concentration of these metabolites in plants can fluctuate according to the variety, development stage, sample treatment, extraction process and the quantification method (Toker, ). The polyphenol content obtained in this study is seven times higher than radish sprouts for similar germination times (Yuan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…() with an enhanced of polyphenols content in the older sprouts. The difference in the concentration of these metabolites in plants can fluctuate according to the variety, development stage, sample treatment, extraction process and the quantification method (Toker, ). The polyphenol content obtained in this study is seven times higher than radish sprouts for similar germination times (Yuan et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Although hyperforin and hypericins have been reported to mainly contribute to the pharmacological effects of Hypericum extracts, flavonoids have also made an important contribution to the antidepressant activity (Gastpar & Zeller, 2005). In this sense, many species of Hypericum from different localities of the world as well as Turkish flora have been investigated for the presence of the chemicals especially in the last decade (Ferraz et al, 2002;Maggi et al, 2004;Ayan et al, 2009;Toker, 2009;Oztürk et al, 2009;Nunes et al, 2010;Cirak et al, 2010). H. aviculariifolium subp.…”
Section: Research Articlementioning
confidence: 99%
“…HT has been used for many years in the Southeast of Turkey to treat stomach disorders (ulcer, gastritis), jaundice, wounds, gingivitis, anemia, reduce fevers and also as an appetative [21,22]. Moreover, HT includes hyperoside, chlorogenic acid, quercetin, quercitrin, rutin, kaempferol (phenolic and flavonoid compounds) which are important for antioxidant capacities [23]. Previous studies have shown us that the seed extracts of Hypericum species have strong antioxidant activities [24,25].This significant antioxidant capacity is what may be beneficial in inhibiting or decreasing the progress of various oxidative stress-induced diseases [23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HT includes hyperoside, chlorogenic acid, quercetin, quercitrin, rutin, kaempferol (phenolic and flavonoid compounds) which are important for antioxidant capacities [23]. Previous studies have shown us that the seed extracts of Hypericum species have strong antioxidant activities [24,25].This significant antioxidant capacity is what may be beneficial in inhibiting or decreasing the progress of various oxidative stress-induced diseases [23]. However, its effects against hepatotoxicity, myelotoxicity and hematotoxicity have not been clarified in detail.…”
Section: Introductionmentioning
confidence: 99%